2021
DOI: 10.1111/josi.12435
|View full text |Cite
|
Sign up to set email alerts
|

Affirmation on the go: A proof‐of‐concept for text message delivery of values affirmation in education

Abstract: The present study offers a proof‐of‐concept for the delivery of values affirmation via text message. In two studies, we tested whether we could distill the typical 15‐minute pen‐and‐paper values affirmation exercise into a brief (∼4 minute) text‐message based exercise. In Study 1 (N = 42), we asked students to identify an upcoming academic stressor. In Study 2, we targeted students (N = 121) who reported that they would be starting a summer internship they expected to be stressful. In both studies, students co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…By blanketing the intervention as we did, we may have increased the chances that those affirmations were timed to coincide with more threats for more students than in prior research. Recent proof-of-concept evidence has shown that affirmations may be delivered in a timely fashion via mobile technology, which could serve as an effective means to deliver affirmations when and to whom they are needed (Manke et al, 2021).…”
Section: Lack Of Moderation By Ethnicity/racementioning
confidence: 99%
“…By blanketing the intervention as we did, we may have increased the chances that those affirmations were timed to coincide with more threats for more students than in prior research. Recent proof-of-concept evidence has shown that affirmations may be delivered in a timely fashion via mobile technology, which could serve as an effective means to deliver affirmations when and to whom they are needed (Manke et al, 2021).…”
Section: Lack Of Moderation By Ethnicity/racementioning
confidence: 99%
“…Fifth, our research demonstrates the potential of mobile technology as a means to deliver psychological interventions that are targeted to people in need, tailored in content to their needs, and timely to when those needs arise (see also, Manke et al, 2021)—key conditions for the efficacy of social psychological interventions (G. L. Cohen et al, 2017).…”
Section: Discussionmentioning
confidence: 87%
“…Fifth, our research demonstrates the potential of mobile technology as a means to deliver psychological interventions that are targeted to people in need, tailored in content to their needs, and timely to when those needs arise (see also, Manke et al, 2021)key conditions for the efficacy of social psychological interventions (G. L. Cohen et al, 2017). This contribution is particularly useful given the trend for increasing distance education (Mupinga, 2005) that has been accelerated by the coronavirus disease 2019 (COVID-19) pandemic (Goldstein, 2020).…”
Section: Self-affirmation and Behavioral Laddermentioning
confidence: 82%
“…Reflecting on important group memberships seems to be a particularly promising way to help those who are suffering in the immediate aftermath of an acute stressor. We hope this work will contribute to a growing evidence-base (e.g., Manke, Brady, Baker, & Cohen, 2020) suggesting that theoretically-informed online manipulations can be effective ways to help people cope with the stress of life.…”
Section: Discussionmentioning
confidence: 99%